2022
DOI: 10.1021/acssynbio.1c00484
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Production of Tocotrienols in Saccharomyces cerevisiae

Abstract: Tocotrienols as important components of vitamin E have attracted increasing attention, with recent progress made in their heterologous biosynthesis, but all as intracellular products. Aiming to further improve the tocotrienol production capacity of engineered yeast and to advance toward industrial fermentation of tocotrienols, we first optimized the synthetic pathway to enhance the tocotrienol yield and then attempted to realize their secretory production by exploring biphasic extractive fermentation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
0
20
1
Order By: Relevance
“…Xu et al improved the efficiency of the extracellular transport of rubusoside by overexpressing the yeast endogenous transporter Pdr11 and transcriptional activator Msn4, thus improving the titer of rubusoside [ 26 ]. Jiao et al simultaneously overexpressed PDR11 and YOL075C , which was favorable for the transport of tocotrienol [ 40 ]. Therefore, we tried to explore some highly efficient endogenous ABC transporters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al improved the efficiency of the extracellular transport of rubusoside by overexpressing the yeast endogenous transporter Pdr11 and transcriptional activator Msn4, thus improving the titer of rubusoside [ 26 ]. Jiao et al simultaneously overexpressed PDR11 and YOL075C , which was favorable for the transport of tocotrienol [ 40 ]. Therefore, we tried to explore some highly efficient endogenous ABC transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, intracellular accumulation of the product remains a problem. Two-phase fermentation may further promote product secretion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results also showed that constitutive overexpression of exporters reduces biomass accumulation in engineered strains. In previous studies, controlling the expression of exporters through a feedback loop or the GAL regulatory system could effectively alleviate the impact on cell growth. It inspired this study to build a quorum sensing system , or a product-responsive biosensor , to regulate the expression of the exporters in the following research to decouple it from the cell growth period and alleviate the metabolic stress and cytotoxicity caused by exporter overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters are widely found in various organisms, including importers for nutrient uptake and exporters for exporting substances from the cytosol to the extracellular environment . Previous studies have shown that ABC exporters in S. cerevisiae are associated with the tolerance and export of heterologous products, such as artemisinic acid and tocotrienols . These results suggested that ABC exporters are likely to have the potential for terpenoid export in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 97%
“…The secretory production of tocotrienols in S. cerevisiae was realized by exploring biphasic extractive fermentation and overexpressing endogenous transporters, with the tocotrienol titer reaching 82.68 mg/L in shake-flask cultures and a secretion ratio of 73.66%. 176 4.3.3. MCFs for Producing Vitamin K2.…”
Section: Mcfs Formentioning
confidence: 99%